2016
DOI: 10.1007/s12192-016-0702-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of immunomodulatory and anti-inflammatory effects of eriodictyol through its cellular anti-oxidant activity

Abstract: Many studies have been performed to assess the potential utility of natural products as immunomodulatory agents to enhance host responses against infection or to ameliorate immune-based pathologies. To determine whether eriodictyol has immunomodulatory effects and clarify which types of immune effector cells are stimulated in vitro, we investigated the stimulatory effect of eriodictyol on spleen cells isolated from BALB/c mice. Eriodictyol significantly stimulated splenocyte proliferation. However, only B lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…For example, M1 (N2, Q2), namely, eriodictyol, a natural avonoid compound present in citrus fruits, has been reported to have broad bioactivities such as antioxidant, anti-inammatory, immunomodulatory and antidiabetic activities. [35][36][37] It is worth mentioning that eriodictyol was found to be one of the most potent insulin secretagogues among hundreds of compounds tested. 38 M19b, namely, hesperidin, a type of citrus bioavonoid distributed in foods including grapefruits, oranges and lemons, has many pharmacological activities, such as antioxidant, anti-depression and antitumour activities.…”
Section: View Article Onlinementioning
confidence: 99%
“…For example, M1 (N2, Q2), namely, eriodictyol, a natural avonoid compound present in citrus fruits, has been reported to have broad bioactivities such as antioxidant, anti-inammatory, immunomodulatory and antidiabetic activities. [35][36][37] It is worth mentioning that eriodictyol was found to be one of the most potent insulin secretagogues among hundreds of compounds tested. 38 M19b, namely, hesperidin, a type of citrus bioavonoid distributed in foods including grapefruits, oranges and lemons, has many pharmacological activities, such as antioxidant, anti-depression and antitumour activities.…”
Section: View Article Onlinementioning
confidence: 99%
“…Eriodictyol is a polyphenol flavonoid widely distributed in fruits and vegetables, mainly found in lemons and peanuts . Previous studies have highlighted multiple pharmacological effects of eriodictyol, including anti‐inflammatory and antioxidant activities . However, few studies have been reported on the effect of eriodictyol on ALI and its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Previous studies have highlighted multiple pharmacological effects of eriodictyol, including anti-inflammatory and antioxidant activities. [16,17] However, few studies have been reported on the effect of eriodictyol on ALI and its mechanism. Therefore, in this study, we examined the protective effect of eriodictyol on ALI and explored its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal dose of eriodictyol in our study was 50 μM, which has been reported as nontoxic in various cell lines, such as macrophage mouse cells, NIH3T3 (fibroblast) cells, and HaCaT (human skin) cells (Lee et al, ). In vivo studies in mice suggested that eriodictyol is antiinflammatory (Zhu et al, ), while in vitro studies in mouse spleen cells showed that this compound has antioxidant properties (Mokdad‐Bzeouich et al, ). In HepG2 cells, eriodictyol increased insulin‐stimulated glucose uptake (Zhang et al, ) and inhibited of c‐Jun N‐terminal kinase (JNK) in macrophages (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%